Unexpected High Ammonia Emissions From Boreal Fires in 2021 and 2023 - Qiwen Chen; Yuanhong Zhao; Bo Zheng; Lin Zhang (Geophysical Research Letters)
Abstract The climate impact of extreme boreal fires in 2021 and 2023 has drawn great attention for their record‐high CO2 emissions. However, their climate impact extends beyond carbon. Fires also emit large amounts of reactive nitrogen, which plays a crucial role in the nitrogen and carbon cycles. Through top‐down inversion of satellite observations, we estimate that the extreme boreal fires in 2021 and 2023 emitted 2.6 Tg N yr−1 and 4.9 Tg N yr−1 of NH3, respectively, which are comparable to agricultural‐intensive regions, making boreal fires the second‐largest contributor to the global reactive nitrogen budget. Unlike tropical fires, which emit more NOx than NH3, boreal fires are characterized by high NH3 emissions. With global warming likely to increase wildfire frequency, the rising NH3 emissions from boreal fires could have significant implications for the nitrogen and carbon cycles in that nitrogen‐limited region, necessitating their consideration in future climate impact assessments.